Staff retirement plan: as amended through September 1967 - International Monetary Fund (1967)
This staff regulation of the IMF was adopted on 30th June, 1948, in order to carry out its purposes, functions and operations for the benefit of the members of its staff
osc 15/04/2019
Loans
Keywords: Retirement; Pensions